Development of the Usage Rating Profile-Web Resource (URP-WR): Using Assessment to Inform Web Resource Selection. Issue 4 (1st October 2020) - Mandracchia, Nina R.; Sims, Wesley A.
Abstract: As technology use continues to rapidly increase, so too does consumer use of web-based resources. While important, accessibility is often overemphasized by users when consuming and evaluating web resources. This prioritization may have particularly negative consequences for the selection of supports or interventions in educational settings. This study outlines the development of Usage Rating Profile-Web Resource (UPR-WR), an assessment designed to support the identification, evaluation, and use of web resources. Additionally, preliminary validity evidence supporting the URP-WR interpretation and use argument (IUA) is presented. Content validation and exploratory factor analyses results yielded an URP-WR comprised of 31 items across four identified factors: plausibility, accessibility, appearance, and systems support. Extracted factors demonstrated acceptable reliability estimates (α = 0.82–0.93) and levels of social validity. This resulting URP-WR stands to provide assessment data that will aid educators in selecting web resources of quality for use in a practical setting.